2023
DOI: 10.1111/mec.17110
|View full text |Cite
|
Sign up to set email alerts
|

Stony coral tissue loss disease intervention with amoxicillin leads to a reversal of disease‐modulated gene expression pathways

Michael S. Studivan,
Ryan J. Eckert,
Erin Shilling
et al.

Abstract: Stony coral tissue loss disease (SCTLD) remains an unprecedented disease outbreak due to its high mortality rate and rapid spread throughout Florida's Coral Reef and wider Caribbean. A collaborative effort is underway to evaluate strategies that mitigate the spread of SCTLD across coral colonies and reefs, including restoration of disease‐resistant genotypes, genetic rescue, and disease intervention with therapeutics. We conducted an in‐situ experiment in Southeast Florida to assess molecular responses among S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 123 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…The family is comprised of seven genera: Symbiodinium (formerly clade A), Breviolum (formerly clade B), Cladocopium (formerly clade C), Durusdinium (formerly clade D), Effrenium (formerly clade E), Fugacium (formerly clade F), and Gerakladium (formerly clade G), each comprised of species and subspecies (Baker, 2003;LaJeunesse and Thornhill, 2011;LaJeunesse et al, 2018;Davies et al, 2023), though Caribbean corals typically only associate with Symbiodinium, Breviolum, Cladocopium, and Durusdinium (Baker, 2003;Van Oppen and Burghardt, 2009). Field observations, histopathology, and laboratory-based and molecular-based studies provide strong evidence of coral-Symbiodiniaceae dysbiosis in response to SCTLD (Landsberg et al, 2020;Deutsch et al, 2021;Meiling et al, 2021;Work et al, 2021;Studivan et al, 2022b;Williamson et al, 2022;Beavers et al, 2023;Studivan et al, 2023).…”
Section: Sctld Causes Symbiodiniaceaehost Disruptionmentioning
confidence: 95%
See 1 more Smart Citation
“…The family is comprised of seven genera: Symbiodinium (formerly clade A), Breviolum (formerly clade B), Cladocopium (formerly clade C), Durusdinium (formerly clade D), Effrenium (formerly clade E), Fugacium (formerly clade F), and Gerakladium (formerly clade G), each comprised of species and subspecies (Baker, 2003;LaJeunesse and Thornhill, 2011;LaJeunesse et al, 2018;Davies et al, 2023), though Caribbean corals typically only associate with Symbiodinium, Breviolum, Cladocopium, and Durusdinium (Baker, 2003;Van Oppen and Burghardt, 2009). Field observations, histopathology, and laboratory-based and molecular-based studies provide strong evidence of coral-Symbiodiniaceae dysbiosis in response to SCTLD (Landsberg et al, 2020;Deutsch et al, 2021;Meiling et al, 2021;Work et al, 2021;Studivan et al, 2022b;Williamson et al, 2022;Beavers et al, 2023;Studivan et al, 2023).…”
Section: Sctld Causes Symbiodiniaceaehost Disruptionmentioning
confidence: 95%
“…Treatment experiments in the British Virgin Islands had a positive effect on the coral community compared to untreated reefs (Forrester et al, 2022), suggesting that treatment might slow the spread of SCTLD across a reef (Neely et al, 2021c;Forrester et al, 2022). Transcriptomic analysis likewise demonstrated that amoxicillin treatments resulted in the reversal of gene expression pathways to a pre-diseased state, possibly benefiting the coral immune response (Studivan et al, 2023).…”
Section: Antibiotic Treatmentsmentioning
confidence: 96%
“…Multiple studies have explored viruses that may infect stony coral symbionts, notably Symbiodiniaceae, but no causative relationships have been detected (Work et al 2021;Veglia et al 2022;Beavers et al 2023;Howe-Kerr et al 2023). Bacterial species are particularly under scrutiny for their potential involvement in SCTLD, due to the effectiveness of antibiotics in halting lesion progression in multiple affected coral species (Aeby et al 2019, Neely et al 2020Shilling et al 2021;Studivan et al 2023). Consequently, SCTLD studies have predominantly focused on understanding changes in the bacterial community between apparently healthy and SCTLDaffected corals.…”
Section: Introductionmentioning
confidence: 99%